MANFAAT GCG PADA PERUSAHAAN PT. JAYA KONSTRUKSI MANGGALA PRATAMA - Raja Osvidius Vincent Saragi Sidabutar (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
The problems that are being faced by various public companies in Indonesia are still weak in managing the company. This is shown by the weak accounting standards and regulations, accountability to shareholders, standards of disclosure and transparency as well as corporate governance processes. This fact indirectly shows the weakness of public companies in Indonesia in carrying out good management to satisfy company stakeholders. An effort is needed to deal with this, one of which is the implementation of Good Corporate Governance. In this study, the type of data used in this research is secondary data. The research method used is a qualitative method which aims to explain a phenomenon in depth and is carried out by collecting data as deeply as possible. For data processing using qualitative methods. Interpretation results can then be used to draw conclusions and provide suggestions related to the implementation of GCG at PT. Jaya Construction Manggala Pratama, Tbk. A risk identification is carried out to determine the effectiveness of GCG implementation at PT. Jaya Construction Manggala Pratama to benefit from the GCG. The SIMPRO JAKON platform can be said to be the implementation of GCG which is beneficial for the sustainability of the company's operations with effective and efficient mitigations.